2000
DOI: 10.1021/bi000282f
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Oxidation of Zinc Finger 2 in Estrogen Receptor DNA-binding Domain Prevents Dimerization and, Hence, DNA Binding

Abstract: For approximately one-third of estrogen receptor (ER)-positive breast cancer patients, extracted tumor ER is unable to bind to its cognate DNA estrogen response element (ERE), an effect that is partly reversible by the thiol-reducing agent dithiothreitol (DTT). Full-length (67 kDa) ER or its 11 kDa recombinant DNA-binding domain (ER-DBD) is also susceptible to loss of structure and function by the action of oxidants such as diamide and hydrogen peroxide; however, prior DNA binding by ER or ER-DBD protects agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 37 publications
6
57
1
Order By: Relevance
“…Although we had only small numbers of subjects in each stratum, we found that the effect of CAT genotype on the association between HRT and breast cancer risk was restricted to ER-positive breast cancer, suggesting that the estrogen response and oxidative stress pathways are somehow intertwined. This result is not unexpected given the fact that binding of ER to DNA is modulated by redox status (36)(37)(38).…”
Section: Discussionmentioning
confidence: 74%
“…Although we had only small numbers of subjects in each stratum, we found that the effect of CAT genotype on the association between HRT and breast cancer risk was restricted to ER-positive breast cancer, suggesting that the estrogen response and oxidative stress pathways are somehow intertwined. This result is not unexpected given the fact that binding of ER to DNA is modulated by redox status (36)(37)(38).…”
Section: Discussionmentioning
confidence: 74%
“…PCa cells can produce increased levels of reactive oxygen species (ROS) and change the redox status of their microenvironment in response to locally produced transforming growth factor β1 (TGFβ1) prooxidant signals as revealed in DU145 PCa cells (54). Interestingly, oxidative stress inactivates ERβ by inhibiting the receptor's dimerization by altering the second zinc-finger motif in the ERβ structure and therefore destabilizing its DNA-binding capacity (55). As a result, ERβ loses its ability to regulate various genes.…”
Section: Erβ and Oxidative Stressmentioning
confidence: 99%
“…These two zinc fingers in ERa DBD function cooperatively in ERa dimerization and DNA binding (25,26). In addition, the COOH-terminal zinc finger of ERa is structurally disordered, and the cysteine thiols of this zinc finger have been characterized as particularly susceptible to the attack of electrophilic agents such as 2,2 ¶-dithiobisbenzamide-1 and benzisothiazolone (27)(28)(29).…”
Section: -Deoxy-dmentioning
confidence: 99%